Profesionalisme Penyelenggara Adhoc dalam Keberatan Saksi di Tahapan Rekapitulasi Hasil Penghitungan Suara Tingkat Kecamatan - Amrullah Amrullah; Subhilhar Subhilhar; Muryanto Amin (Universitas Medan Area, 2021)
The purpose of this research is to answer the professionalism of the District Election Committee (PPK) in carrying out the adhoc district level recapitulation in carrying out the recapitulation at the sub-district level, in particular the follow-up to the witness's objection makes it possible for various problems that cannot be resolved in the recapitulation at the sub-district level, so that they arise again. at the district level. This study uses the main theory of electoral integrity from Pippa Norris. To explain KDP's professionalism, Gregorius Sahdan's theory of professionalism is used. To see the form of resolution of the witness' objection, the theory of conflict resolution from Spiegel, Novri Susan, and Ralf Dahrendorf will be used. The research findings show that the professionalism of KDP in the recapitulation at the sub-district level is very good in terms of regulatory capacity and implementative capacity. Judging from the administrative capacity, there are still several shortcomings due to reduced accuracy as a result of the very high workload and work intensity of KDP. In addition, the witness's objection in the recapitulation at the sub-district level had been properly accommodated by the PPK based on the provisions of the law and PKPU. The model that was used by the PPK to follow up on the objections of witnesses was discussion (consolidation), recommendations from the District Panwaslu (mediation), and through a lawsuit to the Constitutional Court (arbitration). These methods are applied in stages and conditionally.